2016
DOI: 10.1007/s10549-016-3716-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control study of treating secondary stage II breast cancer-related lymphoedema with free lymph node transfer

Abstract: Microsurgical techniques are increasingly used for treating severe lymphoedema cases. The purpose of this study was to evaluate the effectiveness of free vascularized lymph node transfer (LNT) in stage II breast cancer-related lymphoedema patients in comparison with non-surgical management. During the last 3 years, 83 female patients were examined at our lymphoedema clinic. Finally, 36 cases were included in this study and randomly divided in two groups: group A patients (n = 18, mean age 47 years) underwent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 24 publications
3
103
0
10
Order By: Relevance
“…Regarding the vascular pedicle nourishing the lymphatic tissue flap, most published data suggest the use of the superficial circumflex iliac artery and vein as the safest lymphatic pathway; only a few studies raise the issue of the dominant LN flap vascular pedicle . We agree with Gharb et al that the vascular supply of the LN flap must be based on the dominant perforator, which is intraoperatively selected and not always preplanned, ie, either SIEA or SCIA.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Regarding the vascular pedicle nourishing the lymphatic tissue flap, most published data suggest the use of the superficial circumflex iliac artery and vein as the safest lymphatic pathway; only a few studies raise the issue of the dominant LN flap vascular pedicle . We agree with Gharb et al that the vascular supply of the LN flap must be based on the dominant perforator, which is intraoperatively selected and not always preplanned, ie, either SIEA or SCIA.…”
Section: Discussionsupporting
confidence: 59%
“…Hummelink et al presented their experience using the computed tomography angiographies for virtual planning of LN transplantation associated to deep inferior epigastric artery perforator flap breast reconstruction. In the majority of the combined abdominal and lymphatic flaps, they identified only one LN, while it is not mentioned whether they performed a second vascular anastomosis to nourish directly the LN flap; however, it is well‐accepted that separate vascular anastomoses, using dominant pedicles, are preferable to be implemented, in order for the LN flap to be fully revascularized and regain its functionality …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean limb volume was reduced by 57% in the experimental group treated with VLNT versus 18% in the non-surgical control group. Additionally, the rate of infection significantly decreased in the surgically treated group [13,14]. Most recently, a systematic review of 18 studies and 305 patients undergoing VLNT reported improved quality of life in all patients, with 91% improvement of limb circumference, 86% with reduced limb volume, and 60% with improved lymphatic flow [15][16][17][18].…”
Section: Vlntmentioning
confidence: 99%